Themes Underlying Australian General Practitioner Views towards Chiropractic and Osteopathy: An Assessment of Free Text Data from a Cross-Sectional Survey. (14th January 2018) - Grace, Sandra; Engel, Roger; Jalsion, Ian
Abstract : The Australian chiropractic and osteopathic professions underwent a period of significant transformation between 1960 and 2000. This resulted in an improvement in the views held by the medical profession towards the two professions. However, a recent survey of Australian general practitioners (GPs) reported that a number of GPs still hold negative views towards chiropractors and osteopaths. This paper examines these views from the perspective of critical realism and explores the generative mechanisms that can influence the willingness of health practitioners to collaborate over patient care. A qualitative analysis of open-ended responses to a survey of 630 Australian GPs was conducted. Unfavourable attitudes of GPs towards chiropractors and osteopaths included perceived lack of safety, efficacy, and inadequacy of training, despite chiropractic's and osteopathy's reliance on the same evidence base and similar training to those of other manual therapy professions such as physiotherapy. These attitudes may be underpinned by the professional biases against chiropractic and osteopathy that continue to marginalise the professions within the Australian healthcare system. Continued investment in the research base for chiropractic and osteopathic practice is required, along with raising the awareness of GPs about the education and skills of chiropractors and osteopaths.